Optimization of treatment of children with respiratory infections combined with allergic rhinitis - S.P. Kryvopustov (Zaslavsky O.Yu., 2017)
Optimization of treatment both acute viral respiratory infections and allergic diseases is a very actual task in current pediatrics. Allergic respiratory pathology is associated with viral infections. From one hand, allergy is associated with enhanced risk of infection development, from the other viral infection by itself can induce exacerbation of respiratory allergic manifestations. The paper demonstrates the potential of antihistamine L-cet syrup (levocetirizine dihydrochloride) for the treatment of children with respiratory infections but without allergic rhinitis that is a rare phenomenon. Levocetirizine is a left-hand isomer of antihistamine cetirizine II generation and has higher congeniality to H1-receptors compared to it. Besides levocetirisine is a competitive antagonist of H1 histamine receptors; it inhibits producing molecules of intracellular adhesion molecule 1 and rhinovirus replication; it has anti-inflammatory and immune-regulating action.